Fish zona radiata (eggshell) protein: A sensitive biomarker for environmental estrogens - Arukve, Augustine; Knudsen, F.R; Goksøyr, Anders (The National Institute of Environmental Health Sciences, 2016)
Environmental estrogens have recently caused great concern because of their ability to mimic natural hormones and influence vital endocrine functions in humans and wildlife. The induction of vitellogenin (Vtg) synthesis by environmental estrogens in viviparous vertebrates has been proposed as an effective and sensitive biomarker of estrogenicity. Immunochemical analysis of plasma from Atlantic salmon (Salmo salar) exposed to 4-nonylphenol (NP) or to effluent from oil refinery treatment plant (ORTP), shows that NP and ORTP effluent induces Vtg and zona radiata proteins (Zrp) in a dose-dependent manner. However, Zrp-beta cross-reactive proteins are more responsive than Zrp-alpha, Zrp-gamma, and Vtg. The sensitivity of Zrp induction points to the zona radiata proteins as alternate biomarkers of estrogenicity. publishedVersion